Helicobacter pylori in vivo causes structural changes in the adherent gastric mucus layer but barrier thickness is not compromised. Issue 4 (1st October 1998) - Newton, J L; Jordan, N; Oliver, L; Strugala, V; Pearson, J; James, O F W; Allen, A
Abstract : Background —It has been proposed that a pathogenic effect of Helicobacter pylori is a weakening of the protective mucus barrier; however, this remains controversial. Aims —To clarify the effects of H pylori infection on the mucus gel barrier in vivo. Methods —Mucus gel polymeric structure and the thickness of the adherent mucus barrier were measured in endoscopic biopsy samples in subjects with and without H pylori infection. Results —There was a significant 18% reduction in the proportion of polymeric gel forming mucin in the adherent mucus layer in H pylori positive compared with negative subjects. There was no change in the adherent mucus thickness between H pylori positive and negative subjects without gastric atrophy (mean (SD): 104 (26) μm, 106 (30) μm respectively). There was however a significant reduction in mucus thickness in those H pylori positive subjects with underlying gastric atrophy (84 (13) μm, p=0.03) compared with those without atrophy. Conclusions —A partial breakdown in gel forming structure of the gastric mucus barrier does occur in H pylori infection per se but this is insufficient to cause a collapse of the mucus barrier .